The effect of coating architecture and defects on the corrosion behaviour of a PVD multilayer Inconel 625/Cr coating - Daure, J.L.; Voisey, K.T.; Shipway, P.H.; Stewart, D.A. (Elsevier, 2017)
This paper investigates the effect of substrate surface finish and deposition conditions of PVD multilayer Inconel 625/Cr coatings on their ability to act as a corrosion-barrier. The corrosion-barrier performance of the coatings was characterized by potentiodynamic testing and salt-spray testing followed by image analysis of the exposed surface; further coating properties were investigated through XRD, SEM, EDX and scratch testing. The results show that multilayering produced the expected improvement in scratch resistance however it did not affect corrosion behaviour. Interrupting the deposition process did not decrease the defect density. Defect density was observed to reduce with decreasing substrate surface finish. The corrosion barrier performance of the multilayer Inconel 625/Cr coating (bp100 nm) was greatly improved for coatings deposited on a polished substrate. For the multilayer Inconel 625/Cr coating system used in this work multilayering and process interruption did not prevent defects from limiting the corrosion barrier effectiveness of the coatings. Corrosion barrier performance was successfully enhanced by the use of low roughness substrates to minimise the defect density.